Pengaruh Faktor Risiko Kejadian Pneumonia pada Bayi dengan Budaya Panggang ( Se’i ) di UPT Puskesmas Nulle - Ferawati Tulle; Pius Weraman; Yendris K. Syamruth; Shinta Lisa Purimahua; Anderias Umbu Roga (Malahayati Nursing Journal, 2026)
ABSTRACT Pneumonia is a leading cause of infant mortality, especially in areas with high exposure to indoor air pollution and certain cultural practices. The roasting culture (se’i) in Timor Tengah Selatan may increase the risk of pneumonia due to prolonged smoke exposure in enclosed spaces with inadequate ventilation. This study aimed to analyze the influence of risk factors on the incidence of pneumonia among infants in the working area of UPT Puskesmas Nulle. This study used an analytical observational design with a case-control approach involving 154 infants, consisting of 77 cases and 77 controls. Data were analyzed using multiple logistic regression to determine significant factors associated with pneumonia incidence. The results showed that the regression model was significant (p=0.000), with a Nagelkerke R Square value of 0.616 and a classification accuracy of 78.6%. Significant variables associated with pneumonia were nutritional status (p=0.012; OR=3.899; 95% CI=1.345–11.298), vitamin A supplementation (p=0.001; OR=5.610; 95% CI=2.007–15.681), smoking habits (p=0.006; OR=3.974; 95% CI=1.482–10.656), and roasting culture (se’i) (p=0.000; OR=11.033; 95% CI=3.950–30.813) as the most dominant factor. Meanwhile, immunization status, exclusive breastfeeding, housing density, home ventilation, and firewood use were not significantly associated (p0.05). Roasting culture increases infant pneumonia risk. Keywords: Nutritional Status, Pneumonia, Roasting Culture, Smoking Habits, Vitamin A.  ABSTRAK Pneumonia merupakan penyebab utama kematian bayi, terutama di wilayah dengan paparan asap tinggi dan praktik budaya tertentu. Budaya panggang (se’i) di Kabupaten Timor Tengah Selatan berpotensi meningkatkan risiko pneumonia akibat paparan asap dalam ruang tertutup tanpa ventilasi memadai. Penelitian ini bertujuan untuk menganalisis pengaruh faktor risiko terhadap kejadian pneumonia pada bayi di wilayah kerja UPT Puskesmas Nulle. Penelitian ini menggunakan desain observasional analitik dengan pendekatan case-control dengan jumlah sampel 154 bayi yang terdiri dari 77 kasus dan 77 kontrol. Analisis data dilakukan menggunakan regresi logistik berganda untuk mengetahui faktor yang berpengaruh terhadap kejadian pneumonia. Hasil penelitian menunjukkan bahwa model regresi signifikan (p=0,000), dengan nilai Nagelkerke R Square sebesar 0,616 dan akurasi klasifikasi sebesar 78,6%. Variabel yang berpengaruh signifikan terhadap kejadian pneumonia adalah status gizi (p=0,012; OR=3,899; 95% CI=1,345–11,298), pemberian vitamin A (p=0,001; OR=5,610; 95% CI=2,007–15,681), kebiasaan merokok (p=0,006; OR=3,974; 95% CI=1,482–10,656), serta budaya panggang se’i (p=0,000; OR=11,033; 95% CI=3,950–30,813) sebagai faktor paling dominan. Sementara itu, variabel status imunisasi, pemberian ASI eksklusif, kepadatan hunian, ventilasi rumah, dan penggunaan kayu bakar tidak menunjukkan pengaruh yang signifikan (p0,05). Budaya panggang meningkatkan risiko pneumonia bayi. Kata Kunci: Budaya Panggang, Kebiasaan Merokok, Pneumonia, Status Gizi, Vitamin A.